Borers beware! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Insect Science and its Application Special Issue, Volume 21, Number 4, December 2001. ISSN 0191-9040 Published by the ICIPE Science Press